The benefits of using instructor-developed screencasts to support college students’ learning of maths: insights from an Irish case study - Tunku Ahmad, Tunku Badariah; Doheny, Frank; Harding, Nuala; Faherty, Sheila (2013)
This article reports on a case study undertaken to explore college students’ views of the benefits of screencasts in enhancing their Maths learning experience at an Irish institute of technology. A total of 47 screencasts – developed for 14 topics for Year 1, Year 2 and Year 3 mandatory Algebra and Calculus courses taught by one instructor – were uploaded onto the college’s Moodle site for students to access. An open-response survey asking about the benefits of the screencasts and how they helped students to learn the course content was administered online. Out of the total population of 266 students taking the courses, 138 responded to the survey constituting a response rate of about 52%. The data were analysed using an inductive thematic content analysis, in which student feedback was scrutinized and categorized according to the central ideas they shared. Themes that represented different types of screencast use and benefits were generated from this clustering of feedback. Consistent with previous studies, the findings show that a vast majority of students (88.4%) used the screencasts to fulfill myriad learning needs, and viewed the videos as an extremely useful tool that enhanced their Maths learning experience, stating that they were “very helpful,” “very informative,” “easy to follow,” “very practical,” and “a brilliant asset to have.” The narrative data pointed to ten primary benefits of screencasts, which included supporting flexible and personalized learning, supplementing lectures and enhancing understanding of keyskills, delivering a vicarious learning experience, facilitating exam revision and material review, providing multimodal support for Maths learning, helping students to keep track with Maths modules, filling up gaps in notes, serving as a memory aid, providing a tighter match with course content, and making Maths learning more enjoyable. The findings have positive implications for screencasts as a promising tool for Maths learning in future decades.